Живой мир: энциклопедия / Л. Колвин, Э. Спиэр ; пер. с англ. Г. И. Рожковой ; ред. К. Стокли - Колвин Лесли (РОСМЭН, 1998)
Экземпляры: ф15 (20190412) / Инвентарный номер: 194161 / Цена: / Авт.знак: К 60 / ББК: 28.08я2